2013
DOI: 10.3892/or.2013.2498
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine induces apoptosis and inhibits metastasis in MDA-MB-231 human breast cancer cells in vitro and in vivo

Abstract: Breast cancer remains the leading cause of cancer-related deaths among women. Owing to high efficiency and low toxic effects, further exploration of natural compounds from Chinese herbal medicine may be an efficient approach for breast cancer drug discovery. In this study, we investigated the effects of evodiamine on the growth and metastasis of MDA-MB-231 human breast cancer cells in vitro and in vivo. In vitro, evodiamine inhibited cell migration and invasion abilities through downregulation of MMP-9, urokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 35 publications
3
53
0
1
Order By: Relevance
“…In the present study, it was shown that PDGF-BB stimulation significantly increased the levels of phosphorylated p38 MAPK and Erk1/2 in VSMCs, which was inhibited by evodiamine treatment. These findings were in accordance with previous studies involving tumor cells, and suggested that the inhibition of mitogenesis and p-38/p-Erk activity may serve as the molecular basis for the functions of evodiamine (21,27,28). However, the regulation of p38 and Erk activity by evodiamine is cell type-dependent and may be negative or positive.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, it was shown that PDGF-BB stimulation significantly increased the levels of phosphorylated p38 MAPK and Erk1/2 in VSMCs, which was inhibited by evodiamine treatment. These findings were in accordance with previous studies involving tumor cells, and suggested that the inhibition of mitogenesis and p-38/p-Erk activity may serve as the molecular basis for the functions of evodiamine (21,27,28). However, the regulation of p38 and Erk activity by evodiamine is cell type-dependent and may be negative or positive.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the observation that PDGF-BB increased and evodiamine decreased the expression of p21 in the present study was not unusual. Of note, the inhibitory effects of evodiamine on cell cycle progression have been previously observed in various human tumor cell lines, including small-cell lung cancer cells (20), gastric cancer cells (11), breast cancer cells (21), gastric adenocarcinoma cells (22) and cervical carcinoma HeLa cells (23), and are considered to be important in the antitumor action of evodiamine. The data obtained in the present study extends the current recognition of evodiamine, and suggested that the regulation of cell cycle progression by evodiamine may be general and function in a broader range of cell types, including tumor cells and vascular cells.…”
Section: Discussionmentioning
confidence: 97%
“…Du et al (2013) reported that EVO-induced apoptosis was enhanced by its combination with the ERK inhibitor, PD98059, or the p38 MAPK inhibitor, SB203580 [30]. The relationship of MAPK to EVO-induced apoptosis and cell cycle arrest is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Both ERK and p38 are important members of the MAPK pathways for cancer invasion and metastasis, which are involved in the regulation of MMP-2, MMP-9 and uPA in breast cancer (43). Previous research has found that certain natural products can inhibit breast cancer metastasis by downregulated the expressions of MMP-2, MMP-9 and uPA through inhibition of the p38 signaling pathway (44). In the present study, emodin as well as SB203580, a p38-specific inhibitor and PD98059, an ERK specific inhibitor, decreased the activation of p38 and ERK1/2 and the expression levels of MMP-2, MMP-9 and uPA, but the combination treatment of emodin and SB203580 or PD98059 did not obviously alter these inhibitory effects in MDA-MB-231 cells (Figs.…”
Section: Discussionmentioning
confidence: 99%